ANALISIS PERBANDINGAN PERFORMA WEB SERVICE REST MENGGUNAKAN FRAMEWORK LARAVEL, DJANGO, DAN Node JS UNTUK AKSES DATA DENGAN APLIKASI WEBSITE - Abi Amarulloh; Kurniasih Kurniasih; Muchlis Muchlis (LPPM STMIK ANTAR BANGSA, 2023)
In the development of software applications must pay attention to efficiency in terms of resource use, besides thatsoftware applications are very sensitive to delay. One of the factors that can cause delays is the process carried out on the web service, both in terms of software and hardware when processing the web service. Therefore, it is necessary to analyze the performance of web services to find out the differences between each web service by taking into account indicators such as Time Taken for tests, Requests per second, and HTML Transferred. In this study, theauthor made a comparison of the NodeJS (Express), Django and Laravel frameworks to find which framework is suitable for dataaccess with website applications. After conducting research, it was found that the NodeJS (Express) framework has the fastest execution speed while the Django framework has processing speed in the number of requests per second and HTML Transferred, after that it comes third, namely the Laravel Framework with an average success of 60 requests out of 3000, 5000, and 7000 data.